Acylated pelargonidin and cyanidin 3-sambubiosides from the flowers of Aeschynanthus species and cultivars. (December 2021) - Iwashina, Tsukasa; Rahayu, Sri; Sugahara, Kohtaro; Mizuno, Takayuki; Tsutsumi, Chie; Widyatmoko, Didik
Abstract: Thirteen anthocyanins were isolated from the flowers of two Aeschynanthus species, A. fulgens and A. pulcher, and six cultivars, 'Mahligai', 'Mona Lisa', 'SoeKa', 'Redona', 'Freshya' and 'Bravera', and identified as pelargonidin and cyanidin 3- O -sambubiosides and their malonates, succinates, p -coumarates and caffeates, and pelargonidin 3- O -glucoside by acid hydrolysis, HR-MS and NMR. Of their anthocyanins, pelargonidin 3- O -[xylosyl-(1 → 2)-(6''-malonylglucoside)] (2 ), pelargonidin 3- O -[xylosyl-(1 → 2)-(6''-succinylglucoside)] (3 ), pelargonidin 3- O -[xylosyl-(1 → 2)-(6''- E - p -coumaroylglucoside)] (4 ), pelargonidin 3- O -[xylosyl-(1 → 2)-(6''- Z - p -coumaroylglucoside)] (5 ), pelargonidin 3- O -[xylosyl-(1 → 2)-(6''- E -caffeoylglucoside)] (6 ) and cyanidin 3- O -[xylosyl-(1 → 2)-(6''-succinylglucoside)] (9 ) were reported in nature for the first time. Graphical abstract: Image 1 Highlights: Thirteen anthocyanins were isolated from Aeschynanthus species and cultivars. They were identified as acylated pelargonidin and cyanidin 3- O -sambubiosides and pelargonidin 3- O -gluoside. Of their anthocyanins, six were reported in nature for the first time.